Broadband light output enhancement for scintillator using whispering‐gallery modes in nanospheres. Issue 7 (14th April 2014) - Zhu, Zhichao; Liu, Bo; Cheng, Chuanwei; Chen, Hong; Gu, Mu; Yi, Yasha; Mao, Rihua
<x xml:space="preserve">Abstract</x> An array of monolayer of periodic nanospheres is used to efficiently extract the light from a scintillator of high refractive index with broadband capability. Compared with the plain sample without nanospheres, the enhancement of wavelength‐ and angle‐integrated luminescence by 72 and 68% can be achieved under the excitation of ultraviolet and γ‐ray radiation, respectively. The whispering‐gallery modes for the individual sphere and the periodic arrangement are responsible for the enhancement of light extraction. Such a photonic structure is advantageous over the traditional two‐dimensional photonic crystal.